2014
DOI: 10.1016/j.bbadis.2013.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Mutations of cytochrome c identified in patients with thrombocytopenia THC4 affect both apoptosis and cellular bioenergetics

Abstract: Inherited thrombocytopenias are heterogeneous diseases caused by at least 20 genes playing different role in the processes of megakaryopoiesis and platelet production. Some forms, such as thrombocytopenia 4 (THC4), are very rare and not well characterized. THC4 is an autosomal dominant mild thrombocytopenia described in only one large family from New Zealand and due to a mutation (G41S) of the somatic isoform of the cytochrome c (CYCS) gene. We report a novel CYCS mutation (Y48H) in patients from an Italian fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
103
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(111 citation statements)
references
References 16 publications
6
103
1
1
Order By: Relevance
“…The thrombocytopenia phenotype associated with proapoptotic cytochrome c mutations [1,2] suggests that cytochrome c mediated caspase activation may be essential for platelet formation in humans. To investigate the molecular basis of Thrombocytopenia Cargeeg we generated a knock-in mouse expressing mouse G41S cytochrome c in place of mouse somatic cytochrome c .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The thrombocytopenia phenotype associated with proapoptotic cytochrome c mutations [1,2] suggests that cytochrome c mediated caspase activation may be essential for platelet formation in humans. To investigate the molecular basis of Thrombocytopenia Cargeeg we generated a knock-in mouse expressing mouse G41S cytochrome c in place of mouse somatic cytochrome c .…”
Section: Resultsmentioning
confidence: 99%
“…In contrast de Rocco et al . reported that Cycs -/- / Cyct -/- mouse lung fibroblasts expressing mouse G41S cytochrome c were significantly more sensitive to activation of the intrinsic apoptosis pathway compared to Cycs -/- / Cyct -/- mouse lung fibroblasts expressing WT mouse cytochrome c [2]. The reason for the discrepancy between the results with recombinant protein and transduced cell lines is unclear.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There is no description of Cyt c deficiencies per se as mitochondrial diseases, perhaps because they are incompatible with life. To date, only two mutations in the CYC S gene have been described in patients suffering from a rare disease named thrombocytopenia 4 (De Rocco, 2014; Morison, 2008). …”
Section: Mouse Models Of Defect Of the Oxphos Electron Carriersmentioning
confidence: 99%